Direct Medical Cost Analysis of Dengue Patients: A Retrospective Study - Imaniar Noor Faridah; Tuty Lia Syahfitri; Reza Aditya Nugroho; Woro Supadmi; Haafizah Dania; Dyah Aryani Perwitasari (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Dengue infection is an arboviral disease that could lead to severe illness. The incidence of severe dengue will impact patients' financial aspects. As an important clinical feature, platelet level on admission day might contribute to the direct medical cost. Objective: This study aimed to examine the direct medical cost among patients with dengue fever (DF) or dengue hemorrhagic fever (DHF) in Yogyakarta, Indonesia. Methods: This study was a retrospective study conducted in two private hospitals in Yogyakarta, Indonesia. Participants included in this study were hospitalized patients diagnosed with DF or DHF. Data were extracted from medical records and finance departments in each hospital. Results: Among 174 dengue patients included in this study, the mean age of DHF patients (18.44 + 14.87) was lower than in DF patients (23.47 + 18.99). Patients with DHF (4.88 days) also showed prolonged hospitalization compared with DF (4.18 days) patients. In terms of medical cost, DHF patients need a higher dengue treatment cost, which is about 329.74 USD compared to 220.68 USD for DF patients in hospital 2. Mainly related to room charges, which increased by 9.48% in hospital 1 and 66.28% in hospital 2 compared with DF patients. Furthermore, DHF patients with thrombocytopenia on the first day of admission present higher medical costs in terms of laboratory fees (36.08%), medicine (18.17%), and total medical costs (9.84%). Conclusion: Severe form of dengue will contribute to economic burden. Therefore, prevention and adequate treatment are essential to reduce the prognosis of severe dengue and higher medical cost.